Optimization of Quercetin Gel Formulation using Factorial Design Method and Antibacterial Test against Propionibacterium acnes - M. Andi Chandra; Ilham Kuncahyo; Ana Indrayati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Quercetin is a flavonoid from a group of polyphenolic flavonoid compounds. Quercetin can be used as an alternative to acne treatment, predominantly triggered by Propionibacterium acnes. This study aimed to determine the effect and proportion of carbopol 940, propylene glycol, and glycerin on the physical quality of quercetin gel, the ability of the optimum formula in an antibacterial test, and its diffusion using Franz diffusion. This study uses the factorial design method for formula optimization. Optimization was carried out with the parameters of the physical quality of the gel tested, including viscosity, dispersibility, antibacterial, and Franz diffusion. The combination of carbopol 940, glycerin, and propylene glycol affected the physical quality test of quercetin gel, carbopol and glycerin significantly affected viscosity. In contrast, glycerin and propylene glycol significantly affected Franz's dispersion, antibacterial, and diffusion properties. The optimum proportion of the combination of carbopol 940, glycerin, and propylene glycol in the manufacture of quercetin gel using the factorial design method obtained a concentration of carbopol 940 of 0.5%, glycerin of 15%, and propylene glycol of 10%. The optimum formula ability in the antibacterial test was 22.20 mm, and the cumulative percent of quercetin penetrated was 97.91%.